Autoimmune Encephalitis and Autism Spectrum Disorder - Whiteley, Paul; Marlow, Ben; Kapoor, Ritika R.; Blagojevic-Stokic, Natasa; Sala, Regina (Frontiers in Psychiatry, 2021)
The concept of ‘acquired autism’ refers to the hypothesis that amongst the massive heterogeneity that encompasses autism spectrum disorder (ASD) there may be several phenotypes that are neither syndromic nor innate. Strong and consistent evidence has linked exposure to various pharmacological and infective agents with an elevated risk of a diagnosis of ASD including maternal valproate use, rubella and herpes encephalitis. Autoimmune encephalitis (AE) describes a group of conditions characterised by the body's immune system mounting an attack on healthy brain cells causing brain inflammation. The resultant cognitive, psychiatric and neurological symptoms that follow AE have also included ASD or autism-like traits and states. We review the current literature on AE and ASD. Drawing also on associated literature on autoimmune psychosis (AP) and preliminary evidence of a psychosis-linked subtype of ASD, we conclude that AE may either act as a potentially causative agent for ASD, and/or produce symptoms that could easily be mistaken for or misdiagnosed as autism. Further studies are required to discern the connection between AE and autism. Where autism is accompanied by regression and atypical onset patterns, it may be prudent to investigate whether a differential diagnosis of AE would be more appropriate.